2022
DOI: 10.1515/dx-2022-0042
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine in coronavirus disease (COVID-19): a systematic literature review

Abstract: Objectives Coronavirus disease 2019 (COVID-19) is a life-threatening infectious disorder characterized by a sustained prothrombotic state. Since homocysteine is a potential biomarker of thrombotic diseases, the aim of this article is to provide an updated overview on the possible role played by hyperhomocysteinemia in influencing an unfavorable COVID-19 progression. Methods We carried out an electronic search in Medline (PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
6

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 29 publications
1
24
0
6
Order By: Relevance
“…A systematic review and meta-analysis showed that calprotectin levels were significantly elevated in COVID19 patients who develop severe disease, suggesting its prognostic importance ( Udeh et al., 2021 ). Increased homocysteine ​​levels were also recently suggested as a potential biomarker for predicting the risk of progression to serious COVID19 ( Carpene et al., 2022 ). Presepsin was recently introduced as a potential new diagnostic biomarker for sepsis, with a high sensitivity and specificity ( Zou et al., 2014 ).…”
Section: Biomarkers Of Covid19 Severity and Mortalitymentioning
confidence: 99%
“…A systematic review and meta-analysis showed that calprotectin levels were significantly elevated in COVID19 patients who develop severe disease, suggesting its prognostic importance ( Udeh et al., 2021 ). Increased homocysteine ​​levels were also recently suggested as a potential biomarker for predicting the risk of progression to serious COVID19 ( Carpene et al., 2022 ). Presepsin was recently introduced as a potential new diagnostic biomarker for sepsis, with a high sensitivity and specificity ( Zou et al., 2014 ).…”
Section: Biomarkers Of Covid19 Severity and Mortalitymentioning
confidence: 99%
“…(Huang et al 2020) Homocysteine It is one of the alpha-amino acids, which contains sulfur in its composition, and it is not included in the formation of proteins, as it is an intermediate product as a result of the transformation of methionine (Met) into homocysteine (Hou and Zhao 2021) The accumulation of homocysteine in the blood is a serious matter and pathological indication, Homocysteine is converted to methionine by methylation reactions, or it can be converted to cystathionine and then to cytosine by transferring the sulfur group, This reaction requires vitamin B12, folic acid, and the enzyme methylenetetrahydrofolate reductase (MTHFR). (Raghubeer and Matsha 2021) Homocysteine appears as a risk factor for cardiovascular disease and stroke Periodically (Chrysant and Chrysant 2018) Studies show that those with severe infection with Covid-19 had high levels of homocysteine in the blood (Carpenè et al 2022) High levels of Hcy in the blood plasma (>15 μmol/L) is a medical condition Systemic hyperhomocysteinemia (Smith and Refsum 2021) Hypohomocysteinemia (less than 6 μmol/L) occurs in 1-5.0% of Similar to the population, Hcy is also considered an abnormally low concentration of Hcy as a factor Risk to Health Despite the high prevalence of Hcy in dialysis patients A decrease in the blood plasma concentration of Hcy in this patient group is linked to higher hospitalization and mortality rates in terms of maintaining kidneys. (Koklesova et al 2021) Disturbances in the folate-dependent remethylation of Hcy to Met are linked to high Hcy.…”
Section: Introductionmentioning
confidence: 99%
“…Homocysteine It is one of the alpha-amino acids, which contains sulfur in its composition, and it is not included in the formation of proteins, as it is an intermediate product as a result of the transformation of methionine (Met) into homocysteine (Hou and Zhao 2021) The accumulation of homocysteine in the blood is a serious matter and pathological indication, Homocysteine is converted to methionine by methylation reactions, or it can be converted to cystathionine and then to cytosine by transferring the sulfur group, This reaction requires vitamin B12, folic acid, and the enzyme methylenetetrahydrofolate reductase (MTHFR). (Raghubeer and Matsha 2021) Homocysteine appears as a risk factor for cardiovascular disease and stroke Periodically (Chrysant and Chrysant 2018) Studies show that those with severe infection with Covid-19 had high levels of homocysteine in the blood (Carpenè et al 2022) High levels of Hcy in the blood plasma (>15 μmol/L) is a medical condition Systemic hyperhomocysteinemia (Smith and Refsum 2021) Hypohomocysteinemia (less than 6 μmol/L) occurs in 1-5.0% of Similar to the population, Hcy is also considered an abnormally low concentration of Hcy as a factor Risk to Health Despite the high prevalence of Hcy in dialysis patients A decrease in the blood plasma concentration of Hcy in this patient group is linked to higher hospitalization and mortality rates in terms of maintaining kidneys. (Koklesova et al 2021).…”
Section: Introductionmentioning
confidence: 99%